Типология глаголов многоактного cпособа действия (на материале русского и литовского языков) - Галнайтите, Э. (Kalbotyra, 1980)
Multiplicative verbs have no special formal elements in both languages. They are classified into the same Aktionsart on the grounds of a common semantic feature, identical derivational and syntagmatic “behaviour”, and the same relation to the category of aspect.